رأي الدكتور مصطفى الزّلـمي في مسألة النّسخ في القرآن الكريم (بحث مستلّ من رسالة الماجستير) - جلال, إسماعيل محمد; محمّد, عبدالله أحمد (Sulaimani Journal for Humanities, 2022)
The basic content and thought of this research is about the growing worldview and imagination of Dr. Mustafa Zalmi, about one of the sensitive subjects of the Holy Quran, Dr. Zalmi seems to have a set of opinions in this field that are known to them, and because of his research on the Qur'an, he has come to the conclusion that he has a set of his own opinions in this field, It seems that the subject of Naskh has become a lot of branches, from definitions, to shapes and parts, to its conditions, but scientists have generally come to the fact that naskh can happen mentally, and in terms of narration, we have learned that this has happened, But the way it is understood has led to a wide and diverse understanding of this term and its content, but those who are not few consider it forbidden from a legitimate point of view!. All these topics and branches have been discussed in this research and have been discussed, and the evidence in the Holy Qur'an has been brought to this subject. All of these are the themes of this research.